1990
DOI: 10.1111/j.1432-1033.1990.tb19335.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar effects of the protein kinase C inhibitors, staurosporine and H‐7, on cholecystokinin‐induced enzyme secretion from rabbit pancreatic acini

Abstract: The effects of two putative inhibitors of protein kinase C activity, staurosporine and H-7, on partially purified protein kinase C and amylase secretion from isolated rabbit pancreatic acini were investigated. Staurosporine dose-dependently inhibited amylase release stimulated by an optimal concentration of cholecystokinin C-terminal octapeptide. At a concentration of 100 nM, the drug inhibited the secretory response to the secretagogue by approximately 50%. At the same concentration, staurosporine inhibited 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

1992
1992
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
2
10
1
Order By: Relevance
“…The latter authors concluded that protein kinase C could exert a negative feedback role in receptor-mediated pancreatic enzyme secretion. However, as regards pancreatic secretion (Ederveen et al, 1990) and mammary epithelial cell secretion, this hypothesis is not supported by the results obtained with other putative protein kinase C inhibitors.…”
Section: Introductioncontrasting
confidence: 47%
See 2 more Smart Citations
“…The latter authors concluded that protein kinase C could exert a negative feedback role in receptor-mediated pancreatic enzyme secretion. However, as regards pancreatic secretion (Ederveen et al, 1990) and mammary epithelial cell secretion, this hypothesis is not supported by the results obtained with other putative protein kinase C inhibitors.…”
Section: Introductioncontrasting
confidence: 47%
“…It has been shown to dosedependently inhibit the pancreatic secretory response (Ederveen et al, 1990 (Judd et al, 1989 (Caufield and Bolander, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the PKC inhibitor H7 actually potentiates amylase release elicited by CCK and acetylcholine, suggesting that PKC plays an inhibitory role in the control of exocytosis (Pandol & Schoeffield, 1986). Subsequently the more specific inhibitor staurosporine was shown to inhibit secretion partially (Verme et al, 1989;Ederveen et al, 1990), supporting the generally accepted view of PKC as stimulatory in the exocytic pathway. Care should be taken in the evaluation of these data, as staurosporine has been subsequently shown to affect a wide variety of second-messenger systems other than PKC (Ruegg & Burgess, 1989).…”
Section: Introductionmentioning
confidence: 53%
“…'Thus, TPA caused both a narrowing of the dose/response curve for CCKs and an increase in the efficacy of the secretagogue. These observations urged us to investi gate the effects of kinase activation and inactivation on that artificial activation of each one of these two routes tho shape of the dose/response curve for the stimulaonly moderately stimulates secretion [2,4 -X, 11, 14, 15, 19 21, 25, 29, 30], whereas simultaneous activation of both routes mimics the stimulatory effect of the Ca~}-mobilizing seeretagogues [5,19,25], Putative inhibitors of PKC' activity, such as 11-7 and staurosporine, have been used in an attempt to ascer tain the relative importance of both routes in the mech anism of action of the Ca-' -mobilizing secretagogues [7,21,25, 29|. Staurosporine was found to completely inhibit the secretory response to the phorbol ester 12-iMetradeeanoylphorbol 13-acetate (TPA) [7,21.…”
Section: Introductionmentioning
confidence: 99%